Anti-inflammatory activity of psoralen in human periodontal ligament cells via estrogen receptor signaling pathway - Huxiao Li (Nature Portfolio, 2021)
Abstract Psoralen is one of the most effective ingredients extracted from the Chinese herb, Psoralea corylifolia L. Studies have found that psoralen has anti-inflammatory and estrogen-like effects; however, little research has been conducted to elucidate the mechanisms underlying these effects. Through the molecule docking assay, psoralen was found to have a better combination with ERα than ERβ. In human periodontal ligament cells, psoralen was found to upregulate the estrogen target genes (e.g., CTSD, PGR, TFF1) and down-regulate the expression of inflammatory cytokines (TNF-α, IL-1β, IL-6 and IL-8) stimulated by P. gingivalis LPS, as well as TLR4-IRAK4-NF-κb signaling pathway proteins. These effects were reversed by the ER antagonist ICI 182780. These results indicated that psoralen may exert anti-inflammatory effects as an agonist to ER, which could provide a theoretical basis for the use of psoralen for adjuvant therapy and prevention of periodontitis.